Genetic Screening Revealed Latent Keratoconus in Asymptomatic Individuals - Chen, Shihao; Li, Xing-Yong; Jin, Jia-Jia; Shen, Ren-Juan; Mao, Jian-Yang; Cheng, Fei-Fei; Chen, Zhen-Ji; Linardaki, Emmanouela; Voulgaraki, Stavroula; Aslanides, Ioannis M.; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2021)
Purpose: To adopt molecular screening in asymptomatic individuals with high-risk of keratoconus as a combinative approach to prevent subclinical patients from post-refractive surgery progressive corneal ectasia. Methods: In this study, 79 Chinese and 9 Greek families with keratoconus were recruited, including 91 patients with clinically diagnosed keratoconus as well as their asymptomatic but assumptive high-risk first-degree relatives based on underlying genetic factor. Mutational screening of VSX1, TGFBI and ZEB1 genes and full clinical assessment including Pentacam Scheimpflug tomography were carried out in them. Results: Five variants in VSX1 and TGFBI genes were identified in 3 Chinese families and 1 Greek family, and 4 of them were novel ones. Surprisingly, ultra-early corneal changes in Belin/Ambrosio Enhanced Ectasia Display of Pentacam corneal topography together with co-segregated variants were revealed in the relatives who had no self-reported symptoms. Conclusions: Variants of VSX1 and TGFBI genes identified in both the clinically diagnosed and subclinical patients may cause the keratoconus through autosomal dominant inheritance pattern, with different variable expressivity. Combinative genetic and Belin/Ambrosio Enhanced Ectasia Display is capable to identify patients with latent keratoconus. This study indicates that genetic testing may play an important supplementary role in re-classifying the disease manifestation and evaluating the preoperative examination of refractive surgery.